Introduction to the Physics of Silicene and other 2D Materials - Cahangirov, Seymur; Sahin, Hasan; Le Lay, Guy; Rubio, Angel (Lecture Notes in Physics, 2017)
This concise book offers an essential introduction and reference guide for the many newcomers to the field of physics of elemental 2D materials.Silicene and related materials are currently among the most actively studied materials, especially following the first experimental synthesis on substrates in 2012.